KUALITAS MANAJEMEN PENYAKIT KAMBING SAPERA PADA CV BHUMI NARAYA FARM - Edya Moelia Moeis (Universitas Islam Balitar, 2022)
This study aims to determine the nature of the economic value for breeders in maintenance because it does not really need a large area of ​​land, the source of feed is easy to obtain, besides that the advantages of this Sapera goat are fast breeding and relatively high milk production, ranging from 1.5 - 2 liters. per day. In addition, the advantage of this Sapera dairy goat business is that it can provide the availability of community milk and income for farmers. The need for animal protein in Indonesia continues to increase. According to Anonymous (2021), that the average annual per capita milk consumption in 2019 was 2.44 liters/capita/year, in 2020 it was 16.27 liters/capita/year and has increased from 2019. In livestock business goats, of course there are many obstacles that must be faced. The obstacles that must be faced in the maintenance of dairy goats, among others, the emergence of diseases that attack goats. Therefore, health management is one of the most important roles in goat farming. In livestock health management, disease prevention is still the best course of action.